The Role of Notaries in Realizing Effective Implementation Electronic Deed Registration in Tegal Regency - Rahmawati, Desy Tri; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze and understand the implementation of the role of Notaries to find out and analyze the problems in the implementation of electronic deed registration in Tegal Regency and to find out and analyze the role of Notaries in realizing the effectiveness of the implementation of electronic deed registration in Tegal Regency. The type of research used in this study is a type of sociological or empirical legal research that includes legal identification and legal effectiveness, empirical legal research is legal research where data is obtained through primary legal data or data obtained directly in the community. The approach method used is a qualitative method. type of sociological or empirical legal research that includes legal identification and legal effectiveness. This research was conducted with a field study, the author used the interview method (interview). Based on the research conducted, it can be seen that the implementation of electronic HT deed registration in Tegal Regency has not been running effectively, this is indicated by the small number of HT Deeds registered electronically in Tegal Regency. The weaknesses that resulted in the creation of electronic HT deeds in Tegal Regency not yet running due to the fact that in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 5 of 2020 concerning Mortgage Rights Services there is an issue of the authority of Notaries/PPAT which is only limited to making APHT, sociologically the weaknesses are in the form of issues of change time related to errors in old electronic HT registration data when making new electronic HT deeds, the existence of Article 22 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning Head of the National Land Agency Number 9 of 2019 concerning Integrated Electronic Mortgage Rights Services regarding the provision of user names and passwords to other parties can potentially commit legal violations that can harm the HT owner, network maintenance that often makes electronic HT registration problematic or in other words the system often errors making it difficult for the party registering the Electronic HT deed, not all parties have internet facilities and computer devices, for example in remote areas in Indonesia.Keywords: Effectiveness; Electronic; Notary.